HOMOSEXUALITY AND PSYCHOLOGICAL WHOLENESS - Little, Nicholas (PINS-Psychology in Society, 2025)
Clarke, V, Ellis, S J, Peel, E & Riggs, D W (eds) (2010) Lesbian, gay, bisexual, trans and queer psychology. Cambridge: Cambridge University Press. ISBN 978-0-521-70018-4 pbk. Pages xix + 328. For 22 years, Ted Haggard was the charismatic pastor to a congregation of 10,000 at Colorado’s New Life Church. For the better part of eight years, he was a weekly advisor to the administration of George W Bush and an advocate of legislation like the 2006 amendment outlawing gay marriage in Colorado. And for at least three years, Haggard was the regular patron of a male escort with whom he enjoyed smoking crystal meth and masturbating (but nothing more, he swears!) while watching a balanced mix of gay and straight porn.